PENERAPAN PENDEKATAN SAINTIFIK BERBANTUAN POWERPOINT UNTUK MENINGKATKAN HASIL BELAJAR IPA POKOK BAHASAN CAHAYA DAN CERMIN - LUMBU, ALBERT; PANDA, FLORENTINA MARIA (Jurnal Ilmu Pendidikan Indonesia, 2020)
Research has been conducted with the aim to find out (1) improvement of student learning outcomes by using a powerpoint-assisted scientific approach, (2) differences in student learning outcomes improvement between the use of scientific approaches and conventional approaches. This research method is quantitative research, with quasy experimental. The experimental design used was nonequivalent pretest-posttest control group design. The population is 450 students, namely class VIII semester II Jayapura State Junior High School. The sample used was class VIII H and VIII L with a total sample of 74 students. Sampling was used non-probability sampling technique by purposive sampling. Data on learning outcomes are collected through pretest and posttest. The instruments used are multiple choice tests that have been tested for validity, reliability, difficulty level, and distinguishing features. To find out the increase in student learning outcomes n-Gain is used. To see the difference in student learning outcomes improvement taught by a scientific approach assisted by PowerPoint and conventional approaches a statistical analysis of the different test (t-test) was conducted. The results showed that (1) learning with a scientific approach assisted by powerpoint media can improve the learning outcomes of experimental class students with a high category of 0.72 and a control class of 0.61. (2) there are differences in learning outcomes between the experimental class and the control class which indicated a significance value Î± <0.05 which is equal to 0,000.